The Impact of Ownership Structure on Credit Risk of Commercial Banks: An Empirical Study in Vietnam - Phạm Thị Bích Duyên; Phạm Thị Kiều Khanh (My University, 2021)
The Impact of Ownership Structure on Credit Risk of Commercial Banks: An Empirical Study in Vietnam
Keywords: Ownership structure; Credit risk; Commercial banks